Growth Strategy of a Rural Business School: Sustainable Implementation of Online Studies - Bertheussen, Bernt Arne (Sustainability, 2020)
This case study, which uses interventionist action research methodology, first describes key elements of the online business model which was implemented at a business school in Arctic Norway. The aim of the business model intervention was to create a growth in student influx. Next, the study examines the actual impact of the intervention in terms of number of online applicants over the last decade. The findings show that the online courses hit a “nerve” in the Norwegian market for higher education as now more than a thousand students, scattered all over the country, apply for admission. Thereafter, the study investigates why students choose to study online. The results disclose that the main motive for choosing online studies is that they better meet students’ needs for different types of study flexibility. Finally, this research explores whether online studies cannibalizes the traditional campus model in a non-sustainable way. The findings show that online and traditional campus studies do not compete, but instead complement each other as they attract different target groups of students. Online studies serve as an essential channel for lifelong learning as the students were mainly well-educated women who worked full-time or part-time. Finally, strategic insights from the process of launching sustainable online studies by a rural business school are discussed.